Defective porous carbon microrods derived from fullerenes (C70) as high-performance electrocatalysts for the oxygen reduction reaction. Issue 2 (15th December 2021) - He, Zhimin; Wei, Peng; Xu, Ting; Guo, Ziqian; Han, Jiantao; Akasaka, Takeshi; Guo, Kun; Lu, Xing
Abstract : Fullerene (C70 ) molecules are assembled into microrods, and calcination breaks the carbon cages into defect-rich porous carbon microrods that show excellent ORR performance, comparable to commercial Pt/C. Abstract : Disrupting the integrity of the sp 2 -carbon skeleton offers an effective strategy to create active sites for the oxygen reduction reaction (ORR). In this work, fullerene (C70 ) molecules, composed of 12 pentagons and 25 hexagons all bonded by sp 2 -C atoms, are assembled into microrods (C70MRs) at the liquid–liquid interface and then broken down by calcination to generate metal-free fullerene-derived ORR electrocatalysts. The effect of the pyrolysis temperature on C70MRs is investigated, and it is found that pyrolysis at 900 °C effectively unfolds the C70 cages and converts them into a highly porous, defect-rich carbon material (C70MRs-900) with the rod-shaped morphology well-retained. These structural features endow C70MRs-900 with outstanding ORR activity and stability together with remarkable methanol tolerance, better than C70MRs annealed at either lower (800 °C) or higher (1000 °C) temperatures. Furthermore, nitrogen atoms are successfully incorporated into the defective carbon skeleton by annealing C70MRs at 900 °C in the presence of NH4 Cl. The resultant N-doped C70MRs-900 exhibits remarkable ORR performance with a half-wave potential of 0.836 V, comparable to that of the commercial 20% Pt/C catalyst. This work presents a simple and effective route of utilizing fullerene molecules as starting materials to develop high-performance metal-free, carbon-based electrocatalysts toward the ORR and even beyond.